Innovation management in higher education as a factor of regional economic growth - R. A. Abramov (Вестник университета)
Innovation activity in higher education serves as a catalyst for economic growth at the regional level. Modern economic realities require active introduction of scientific and technological achievements in the educational process, which inevitably affects regional economic development. The increasing contribution of higher education institutions to regional economy is due to a number of factors such as education quality improvement, research activities development, and scientific developments commercialization. The Education Development State Program data, examples of the world’s leading universities and reports on the research activities of Russian universities for 2015–2022 have been analyzed, and a multi-parametric assessment of innovative projects effectiveness in higher education carried out. The study included a comparative analysis of investments in scientific research and their impact on the regional gross domestic product, as well as the analysis of scientific developments commercialization cases. Between 2015 and 2022 the amount of funding for scientific research in leading Russian universities increased by 37 %, which was accompanied by an increase in the number of patents by 24 % and commercially successful projects by 18 %. The examples of St. Petersburg and Novosibirsk universities show an increase in direct investment in the regions by 15 and 20 %, respectively, due to scientific developments commercialization. The study also shows that the average growth of regional gross domestic product in regions with active innovation activity in universities amounted to 5.6 % per year.